2005
DOI: 10.1021/la050114u
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Manganese and Molybdenum Mixed Oxide Thin Films and Their Charge Storage Properties

Abstract: Manganese and molybdenum mixed oxides in a thin film form were deposited anodically on a platinum substrate by cycling the electrode potential between 0 and +1.0 V vs Ag/AgCl in aqueous manganese(II) solutions containing molybdate anion (MoO(4)2-). A possible mechanism for the film formation is as follows. First, electrooxidation of Mn2+ ions with H2O yields Mn oxide and protons. Then, the protons being accumulated near the electrode surface react with MoO(4)2- to form polyoxomolybdate through a dehydrated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
111
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(124 citation statements)
references
References 40 publications
(63 reference statements)
9
111
0
Order By: Relevance
“…2a, the unmodified GC electrode exhibits no feature associated with FA, confirming no activity of GC toward oxidation of FA. H-and L-Bir/GCs in the absence of FA provide pseudocapacitive characteristics in the whole potential region examined, which can be attributed to continuous redox reactions of Mn 4+ /Mn 3+ accompanied with insertion/deinsertion of protons or electrolyte metals (Na + in the present case) into/from the oxide film [21]. The capacitive response of L-Bir/GC is larger than that of H-Bir/GC, probably reflecting its larger electroactive area.…”
Section: Fa Detectionmentioning
confidence: 70%
See 1 more Smart Citation
“…2a, the unmodified GC electrode exhibits no feature associated with FA, confirming no activity of GC toward oxidation of FA. H-and L-Bir/GCs in the absence of FA provide pseudocapacitive characteristics in the whole potential region examined, which can be attributed to continuous redox reactions of Mn 4+ /Mn 3+ accompanied with insertion/deinsertion of protons or electrolyte metals (Na + in the present case) into/from the oxide film [21]. The capacitive response of L-Bir/GC is larger than that of H-Bir/GC, probably reflecting its larger electroactive area.…”
Section: Fa Detectionmentioning
confidence: 70%
“…The electrode coated with highly crystallized film gave rise to pseudocapacitive properties [21]. In this study, we found that the similarly-prepared film but composed of small birnesite crystallites exhibits high catalytic activity toward FA oxidation, which can be successfully applied to determine the concentration of FA.…”
Section: Introductionmentioning
confidence: 86%
“…It was found in the literature that the incorporation of Ni [28,29], Pb [28], Mo [30], and V [31] oxides could enhance the specific capacitance of the Mn oxide. Nevertheless, the effects of Co oxide addition were not extensively studied [29,[32][33][34], and the experimental results from different research groups varied significantly.…”
Section: Introductionmentioning
confidence: 99%
“…They believed that the free electron metal atoms as electron donors can change the electronic structure of MnO 2 for a better conductivity and high capacitive performance. In fact, the doped materials do show better performance in magnetic, electrical and electrochemical properties, for example, cyclic voltammetry of the Mn/Mo oxide film-coated electrode exhibits a pseudocapacitive behavior with higher capacitance and better rate capability than that of the pure Mn oxide prepared similarly [15]. It is believed that if the radii of doping ion is lower but not so much than that of Mn 3+ ion and the bond between doping ion and O 2À is stronger than Mn-O bond, partial substitution of Mn 3+ ions may induce the reduction of lattice constant and the increase of Mn oxidation state, consequently, improving electrochemical properties [11,12].…”
Section: Introductionmentioning
confidence: 99%